Choice Implies Meaning: The "Imperatival Participles" of 1 Peter. - Miller, Timothy E. (Novum Testamentum, 2022)
That 1 Peter uses participles where imperatives are expected is clear. Why it does so is not. Scholarly discussion has focused on whether the participles are independent or dependent. Early grammarians argued that these participles were dependent but struggled to explain why the participles appeared far from their head verb. Modern grammarians have argued that they are independent, yet they have given insufficient attention to why the participle is used instead of the imperative. This article suggests a path forward, which vindicates the earlier interpretation by providing a discourse explanation for the "imperatival participles." Stated simply, the participle is operating according to its normal function by structuring the discourse. That the participles in 1 Peter are far from their head verb shows the complex structuring of the letter, with the main imperatives moving the discourse along and the participles expressing ways that those head verbs may be accomplished.